PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 21 BALAI MAKAM KECAMATAN MANDAU - Sari Mardiah; Mahmud Alpusari; Zairul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the student achievement of sains studiesthree graderes SD Negeri 21 Balai Makam still low with an average value of 62,5 and KKM social studies is 65. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Based on the conduct of research with the implementation of learning models obtained results koopertif Make a Match type of activity the teacher in the lerning process in cycle I frist meeting was 75% and at the second meeting of teacher activity increased to 87,5%. cycle II first meeting and the second meeting of activity increased to 91,67% and the second meeting of activity increased to 95,83%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 70,83% and at second meeting of activity increased to 79,17% and a second meeting of activity increased to 85,7%. At the first meeting of the second meeting of activity increased to 95,83%.This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 62,5. In the first cycle improve an average of 68,67and an impove in the second with an average of 81,33. Result in the research that the implementation of cooperative learning model of Make a Match can improve students achievement of social Studies at three graderes SD Negeri 21 Balai Makam Kecamatan Mandau.Key Words: Model Learning Make a Match, Sains learning outcomes.